Differential Involvement of Lateral Semicircular Canal and Otolith Organs in Common Vestibular Disorders - Kim, Yehree; Kang, Byung Chul; Yoo, Myung Hoon; Park, Hong Ju (Frontiers in Neurology, 2022)
Semicircular canal and otolith functions came to be evaluated recently, but comprehensive and comparative analysis of canal and otolith dysfunction in common vestibular disorders is lacking. We aimed to analyze the abnormal rates of canal and otolith function in common vestibular disorders. We enrolled 302 patients who were managed for 2 months in a dizziness clinic. Results of caloric, video head impulse test (vHIT), and cervical and ocular vestibular evoked myogenic potential (cVEMP and oVEMP) tests were analyzed and compared among various diagnoses. Vestibular disorders diagnosed included recurrent vestibulopathy (RV, 27%), vestibular migraine (VM, 21%), benign paroxysmal positional vertigo (BPPV, 17%), Meniere’s disease (MD, 11%), vestibular neuritis (VN, 10%), orthostatic dizziness (7%), and central lesions (3%). Lateral canal dysfunction was found most in VN (100%) and less commonly in definite MD (75%), RV (46%) and definite VM (29%). Abnormal caloric results were more common than abnormal vHIT in all disorders. Otolith dysfunction was found more frequently than lateral canal dysfunction in most vestibular disorders except VN. An abnormal cVEMP was more frequent in definite MD than the other disorders. Isolated otolith dysfunction without lateral canal dysfunction was the most found in BPPV, followed by definite VM, RV, and definite MD in decreasing order. Various patterns of involvement in canal and otoliths were revealed in vestibular disorders, suggesting different pathogenesis.